Pemanfaatan Internet Dalam Memasarkan Hasil Usaha Mikro Kecil Dan Menengah (UMKM) Di Kecamatan Medan Labuhan - Dody Hidayat; R Ramli; Uun Novelia Harahap (LPPM STIKOM Tunas Bangsa, 2021)
The internet in the business world is used for information exchange, product catalogs, promotional media, electronic mail and mailing lists. The internet can also be used as a forum for dialogue, discussion and consultation with consumers online. The use of the Internet for business transaction activities is better known as Electronic Commerce (E-Commerce). In the business world, a website in the form of E-Commerce has become a necessity because there are various benefits that E-Commerce has, including that consumers do not need to come directly to the store to choose the goods they want to buy and for companies to carry out promotional activities and transactions for 24 hours. hours with unlimited range. This community service is carried out with the socialization method, namely lectures, demonstrations and questions and answers, the material is packaged in powerpoint and displayed using infocus. The results of the activities that have been carried out have gone well and smoothly, the interest and enthusiasm of the participants is very high, this can be seen from the activeness of the participants in participating in the socialization by asking questions when the question and answer session opens.